Social Wasps (Vespidae: Polistinae) in an Urban Park from Piauí, Brazil - Santos, Luan V. B.; Monteiro, Daniel P.; Sousa, Caroline F. A. F.; Araújo, Michelly D. F.; Fontes, Lucia S.; Somavilla, Alexandre (Entomological Communications, 2021)
Studies of social wasps (Vespidae: Polistinae) in Piauí State are scarce and only two have been carried out. Due to the lack of studies, we surveyed the wasp species in the Zoobotanical State Park in the urban area of Teresina, Piauí, Brazil. From December 2017 to May 2018, 10 expeditions were carried out using active collection with entomological nets and attractive traps with guava juice. A total of 282 individuals were collected distributed in six genera and 12 species. Parachartergus fraternus Gribodo, 1892 and Synoeca surinama (Linnaeus, 1767) are new records for Piauí, which now has 12 genera and 24 species registered for the state. Such data reveals the need to continue studying Polistinae in Piauí, in order to determine their real species distributions, help conserve natural areas and accurately manage these sites.